WAIS Divide Ice-Core Aerosol Records from 1300 to 3404 m - Mcconnell, Joseph (IEDA: US Antarctic Program Data Center, 2017)
Abstract: A state-of-the-art continuous ice core analytical system was used to analyze ~3 cm by ~3 cm longitudinal samples from ~1300 to ~3404 m depth in the recently collected WAIS Divide deep ice core from West Antarctica. Interpretation of these records and publication of findings is ongoing.